The Journey of a Hospital Gown: Performing Needlework - Richardson, Jennifer Talia Frances (Disability Studies Quarterly, 2016)
This essay explores issues surrounding psychiatric hospitalization through the intersection of creative writing and artmaking. The writing reflects on four artworks by the author created from appropriated hospital gowns that reflect on issues of representation and historical and contemporary experiences of hospitalization for mental disabilities including questions surrounding dignity, wellness, family, asylum tourism, psychiatric photography, and objectification.